A study on the association of systemic fluoride intake and osteoporosis among persons drinking high and low fluoride concentrations in the water - Galang, Emiliana O.
Fluoride in water has been widely used for its dental health benefits and for prevention of dental caries, but concerns have been raised about its skeletal risks and the effects on the bone mineral density and rates of fracture. These alarming issues about fluoride have led the researchers to the question: Is there an association between high fluoride intake manifested by dental fluorosis and risk for osteoporosis among persons drinking high and low fluoride concentrations in their drinking water. To answer this, the researchers decided to determine the possible association between fluorosis and risk for osteoporosis through a cross-sectional study. Two groups were compared. These were the residents from San Antonio, Cavite representing a high fluoride level area (1.8 ppm) in their drinking water and residents from Mariveles, Bataan representing a low fluoride level area (0.182mg/L). The participants consisted of women aged 35-44 years old. They were asked to sign a consent form and to answer a set of questionnaire. An oral examination was conducted to detect levels of dental fluorosis. Bone scanning test was then administered with the use of a Pixi machine to measure the bone mineral density of the calcaneus. Results were gathered and interpreted through T-test. Correlation was established by the use of Paired Sample Correlational Test. An inverse relationship was established which means when fluorosis goes up, bone mineral density goes down. This was particularly true among San Antonio, Cavite subjects. Thus, the result also implies that the fluoride levels in the body can alter bone density that increases one's fracture risks.